EFFECT OF DIGITAL LEARNING STRATEGIES ON STUDENTS’ ACADEMIC PERFORMANCE AND RETENTION OF SELECTED EDUCATIONAL TECHNOLOGY CONCEPTS - Jibril, Mohammed (Jurnal Tatsqif, 2024)
Digital learning strategies, such as Moodle and hybrid learning, are increasingly utilized to enhance academic performance and retention. However, there is limited evidence of their specific effect on Educational Technology courses in Kwara State Colleges of Education. This study addresses this gap by determining the effectiveness of these strategies on students' academic performance and retention. A purposive sampling technique was employed to select the intact class of 200-level computer science education students from two randomly selected colleges. 127 students participated, 65 in the Moodle group and 62 in the hybrid learning group. A quasi-experimental design with pre-test and post-test was adopted, using ANCOVA for the analysis of performance and retention, and independent samples t-test for gender-based comparisons. Kuder-Richardson (KR-20) reliability values of 0.73 for multiple-choice items and a Split-half reliability coefficient of 0.78 for completion tests were obtained. Findings revealed a significant difference in performance (F (1, 124) = 30.10, p < .05), and retention (F (1, 124) = 22.41, p < .05) between students taught with Moodle and those using hybrid learning. Gender had no significant impact on students' academic performance in either learning group. The study concluded that Moodle-based learning improved students' performance and retention more effectively than hybrid learning. It is recommended that Kwara State Colleges of Education adopt Moodle-based learning strategies while continuing to incorporate hybrid approaches for enhanced educational outcomes. Further studies should explore the long-term impacts of these learning strategies across various educational levels.